Party System Change and the Quality of Democracy in East Africa - Riccardo Pelizzo; Zim Nwokora (African Governance and Development Institute (AGDI), 2017)
The purpose of this paper is to explore in greater detail the nexus between party system change and democratic qualities. In doing so, we do not simply assess whether, how and to what extent qualities of democracy in East Africa are affected by the instability of the patterns of inter-party competition (fluidity of the party system), but we also plan to show how the sub-components of party system fluidity (frequency of change, scope of change, variety of change) influence the democratic qualities. By disaggregating fluidity in its constitutive elements and by testing how each of them affects the qualities of democracy, we find that while the frequency of change has a beneficial impact on the qualities of democracy, the other sub-components of fluidity—namely, the “scope” and “variety” of system change—have a consistently negative effect on democratic quality.
Keywords: D02; D72; H00; H11; H89; O00; O10; O43; O55; 330; party system change; East Africa; South East Asia; fluidity; democracy